Some remarks about horizontal, slant, parabolic and polynomial asymptote - Janaszak, Tadeusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
In the teaching of calculus, we consider horizontal and slant asymptote. In this paper the idea of asymptote of function is expanded to polynomials. There are given formulas of coefficients of the multinomial asymptote of the function and some examples of parabolic and cubic asymptote.
Didactics of Mathematics, 2013, Nr 10 (14), s. 45-56
Keywords: Horizontal asymptote; slant asymptote; parabolic asymptote; cubic asymptote; multinomial asymptote; rational function